Atividade antagonista de Acinetobacter baumannii contra amostras de Acinetobacter resistentes a drogas antimicrobianas - Natália Rocha Guimarães (2016)
The search for new antimicrobial substances, especially naturally occurring ones, are gaining great prominence, being the target of several studies, in particular due to the emergence of multiresistant microorganisms, as well as their association with the occurrence of outbreaks. Acinetobacter baumannii is a bacterium of great clinical relevance, that markedly shows multidrug resistance. The aim of this study was to evaluate and to characterize the antagonistic activity of A. baumanni. Among the 19 tested strains, only one, A. baumannii 397, expressed antagonism. Activity was observed exclusively against isolates of the same species. The interference of bacteriophages, fatty acids, residual chloroform and hydrogen peroxide in the interpretation of data was evaluated. In order to optimize antagonism expression, the producer strain was cultivated under different conditions. When grown at 25 °C, larger and clear inhibition zones were generated. Protein extraction of A. baumannii 397 was performed by acid precipitation with HCl 5N. The antagonistic activity was confirmed by the spread plate technique against a clinical isolate of A. baumannii. The crude extract showed antagonist activity of 1280 AU/mL. The extract was inactivated by proteases and remained active after exposure to organic solvents and a broad pH range and temperatures. CIM and CBM values showed bactericidal activity against the indicator strain. The crude extract was submitted to three steps of reverse-phase chromatography, the first step in a C-8 column and the others in a C-18 column. The last chromatographic step generated two active fractions, C5 and C6, eluted with approximately 80% acetonitrile. These fractions were submitted to MS. Five molecular masses were detected in C5, and in C6, two molecular masses of 6.2 kDa and 8.3 kDa. The results showed the synthesis of hydrophobic antimicrobial proteinaceous substance(s), active(s) against multidrug-resistant bacteria, by A. baumannii 397, property not yet described for this species, that displays biotechnological potential.